Analisis Pengaruh Kualitas Fasilitas Fisik dan Non Fisik Pasar Mardika terhadap Niat Berperilaku Konsumen di Kota Ambon - Sammy Saptenno (Jurnal Administrasi Terapan, 2022)
This study aims to examine and analyze the influence of the quality of physical and non-physical facilities at Mardika Market in Ambon on consumers' behavioral intentions in Ambon City. The research is motivated by consumer complaints regarding inadequate market facilities, which have led to a decline in public interest in shopping at Mardika Market.A quantitative approach was employed using a survey method, involving 100 respondents from the Ambon City community. Data were analyzed using multiple linear regression.The results show that both physical and non-physical facility quality significantly affect consumers’ behavioral intentions. The revitalization of Mardika Market is crucial to enhance its competitiveness and attract consumers back.Keywords: physical facilities; non-physical facilities; behavioral intention; market; consumer